1975
DOI: 10.1042/bj1450379
|View full text |Cite
|
Sign up to set email alerts
|

The co-polymeric structure of pig skin dermatan sulphate. Distribution of L-iduronic acid sulphate residues in co-polymeric chains

Abstract: 1. Pig skin dermatan sulphate was degraded by periodate oxidation followed by alkaline elimination or by chondroitinase-ABC to quantify irregular repeating units, i.e. those containing D-GlcUA (D-glucuronic acid) and L-IdUA-SO4 (sulphated iduronic acid). 2. Previous results of periodate oxidation (Fransson, 1974) indicated repeating sequences in pig skin dermatan sulphate containing, on average, 3D-GlcUA, 9 L-IdUA-SO4 or 28 L-IdUA units in addition to N-acetylgalactosamine sulphate. However, complete digestion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1976
1976
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 16 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…DS has previously been indicated to contain high levels of IdoA-GalNAc4S repeats, with lower levels of IdoA2S-GalNAc4S and GlcA (β1-3) GalNAc6S (β1-4) repeats (35,36,(44)(45)(46). Previous tandem mass spectrometric analysis on the DS preparations investigated in this work showed that the abundances of CSB-like repeats was found to be 90.0%, 75.0%, and 50.0% for DS18, DS36, and DS50 respectively (47).…”
Section: Discussionmentioning
confidence: 99%
“…DS has previously been indicated to contain high levels of IdoA-GalNAc4S repeats, with lower levels of IdoA2S-GalNAc4S and GlcA (β1-3) GalNAc6S (β1-4) repeats (35,36,(44)(45)(46). Previous tandem mass spectrometric analysis on the DS preparations investigated in this work showed that the abundances of CSB-like repeats was found to be 90.0%, 75.0%, and 50.0% for DS18, DS36, and DS50 respectively (47).…”
Section: Discussionmentioning
confidence: 99%
“…7). While such sequences have been described in dermatan (37,38), they represent minor components in the mature proteoglycan. The selective sulfation of IdoUA-GalNAc that is flanked by GlcUA-GalNAc suggests that sulfation of GalNAc in dermatan is immediately followed by the epimerization of GlcUA to IdoUA.…”
Section: Identification Of a Murine Orf Encoding The Mouse Ortholog Omentioning
confidence: 99%
“…Sulfated glucuronic acid has not been reported in these polymers previously, but sulfated iduronic acid residues have been identified in pig skin dermatan sulfate (Fransson et al, 1974a,b;Coster et al, 1975) and shark cartilage . In pig skin the iduronic acid sulfate is linked to an unsulfated GalNAc residue (Ciister et al, 1975), a sequence not found in the present work.…”
Section: Discussionmentioning
confidence: 98%
“…(iduronic acid-Nacetylgalactosamine 6-or 4-sulfate),; (5) higher oligosaccharides containing iduronic acid and N-acetylgalactosamine 4-sulfate. Coster et al, 1975;Malmstrom et al, 1975a). All of these polymers occur as protein-polysaccharides in which the repeating disaccharide units are linked to a core protein through a unique galactosyl-galactosyl-xylose linkage region (Roden & Horowitz, 1978).…”
mentioning
confidence: 99%